Documents on British foreign policy, 1919-1939. (London London London London)
8 cilt (1. c. xxxvi, 602, [1] sayfa ; 3. c. xxvi, 617 sayfa ; 5. c. lxxxix 908 sayfa ; 6. c. lxxxv, 995, [1] sayfa ; 7. c. lxxxvi, 808 sayfa ; 8. c. lxxv, 1044, [1] sayfa ; 10. c. lxxxiv, 833 sayfa ; 11. c. lxvii, 597, [1] sayfa)